Pseudomonas aeruginosa in otitis media - Umar, Jidda B; Ibrahim, Muhammad M.; Tom, Isyaka M.; Umoru, Askira M; Isa, Tijjani (International Journal of Medicine, 2016)
Background: Over 50% of cases of otitis media are caused by bacteria and Pseudomonas aeruginosa is the most common aetiologic agent implicated in the pathology of the disease.Objectives: This study is designed to examine the influence of Pseudomonas aeruginosa in otitis media disease, and further look at the susceptibility pattern of the organism to commonly prescribed antimicrobial drugs.Methods: Eighty two (82) swab samples were randomly collected from otitis media patients attending the ENT clinic of the University of Maiduguri Teaching Hospital and cultured for bacterial recovery. Further biochemical tests were conducted. Antimicrobial susceptibility test was performed and susceptibility pattern recorded.Results: Nineteen (19) samples yielded growth of Pseudomonas aeruginosa, which gives a recovery rate of 23.2%. The rate was higher among males (12.2%) than females (11.0%). The rate of isolation was highest among patients of the age category of 0-14yrs (11.0%) and least among those of >44yrs (2.0%). Isolates were highly sensitive to Ciprofloxacin, Ofloxacin and Peflacin but highly resistant to Nalidixic acid and Ampicillin.Conclusions: The infection is highest among children whose immune competence is still developing and as such, it is recommended that treatment should be based on results obtained from in-vitro susceptibility test, and that combination therapy should be considered to forestall chances of emergence of drug resistance.